Decreased Expression of Integrin Subunits α3, α6, and α8 in the Branching Airway Mesenchyme of Nitrofen-Induced Hypoplastic Lungs - Takahashi, Toshiaki; Friedmacher, Florian; Zimmer, Julia; Puri, Prem (European Journal of Pediatric Surgery, 2018)
Introduction Pulmonary hypoplasia (PH), characterized by smaller lung size and reduced airway branching, remains a major cause of neonatal mortality in newborns with congenital diaphragmatic hernia (CDH). Integrin-mediated cell–matrix interactions play an essential role in the fetal lung mesenchyme by stimulating branching morphogenesis. Mice lacking integrin subunits α3 (Itga3) and α6 (Itga6) exhibit severe PH. Furthermore, Itga8-knockout mice show defective airway branching, suggesting that Itga3, Itga6, and Itga8 are crucial for fetal lung development. We hypothesized that expression of Itga3, Itga6, and Itga8 is decreased in the branching airway mesenchyme of hypoplastic rat lungs in the nitrofen-induced CDH model.Materials and Methods Time-mated rats received nitrofen or vehicle on gestational day 9 (D9). Fetuses were sacrificed on D15, D18, and D21, and dissected lungs were divided into control and nitrofen-exposed specimens (n = 12 per time-point and group, respectively). Pulmonary gene expression of Itga3, Itga6, and Itga8 was analyzed by quantitative real-time polymerase chain reaction. Immunofluorescence double-staining for Itga3, Itga6, and Itga8 was combined with the mesenchymal marker Fgf10 to evaluate protein expression and localization in branching airway tissue.Results Relative mRNA expression of Itga3, Itga6, and Itga8 was significantly decreased in lungs of nitrofen-exposed fetuses on D15, D18, and D21 compared with controls. Confocal laser scanning microscopy showed markedly diminished immunofluorescence of Itga3, Itga6, and Itga8 mainly in mesenchymal cells surrounding branching airways of nitrofen-exposed fetuses on D15, D18, and D21 compared with controls.Conclusion Decreased expression of Itga3, Itga6, and Itga8 in the pulmonary mesenchyme may lead to disruptions in airway branching morphogenesis, thus contributing to PH in the nitrofen-induced CDH model.
Keywords: integrin; lung branching; pulmonary hypoplasia; congenital diaphragmatic hernia; nitrofen